The Impacts of Education Level on Financial Literacy and Financial Behaviours: The Case of Women Entrepreneurs - Fitriaty Fitriaty; Shofia Amin; Muhammad Haris Saputra (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2023)
Financial literacy is a person's ability to understand and manage personal finances effectively. High education and financial literacy will certainly influence financial behavior. Women entrepreneurs are a crucial group in the economy of a country, especially in Indonesia. The research objective was to examine the effect of education level on financial literacy and financial behavior of women entrepreneurs in Jambi. This research was quantitative research by using primary data in the form of a questionnaire given to female entrepreneurs in Jambi as respondents using the accidental sampling technique and Slovin's formula that obtained a total of 100 respondents. The data were analyzed using Smart PLS. The results obtained in this research, the education level had a significant positive effect on financial literacy and financial behavior. Furthermore, financial literacy could mediate between the education level and financial behavior of women entrepreneurs in Jambi.